Pemanfaatan Limbah Cair Aren untuk Pupuk dengan Berbagai Starter Dekomposisi terhadap Pertumbuhan dan Hasil Jagung - Ahmad Nurcahyo; Supriyono Supriyono; Purwanto Purwanto (Agrosains : Jurnal Penelitian Agronomi, 2015)
Sugar palm (Arenga pinnata) flour industry in Tulung, Klaten district is the center of the sugar palm flour production industry in Central Java. In the processing of sugar palm flour is a lot of obstacles, one of which is environmental pollution resulting from waste liquid produced. This reasearch was purposed to determine the effect of liquid organic sugar palm fertilizer with a variety of decomposition starters on the growth and yield of maize. The research was held from September to December 2014 at the Greenhouse of Faculty of Agriculture, Sebelas Maret University (UNS) of Surakarta with the design used was Randomized Complete Block Design (RCBD) that there is one factor, that is a variety of decomposition starters. The treatment of each repeated four times in order to obtain 24 plots. The results showed that fertilization using sugar palm liquid waste fermented with variety of decomposition starters have no significant effect on the growth and yield of maize. The combination treatment of sugar palm liquid waste fertilizer fermented with EM-4 resulted higher yield potency grain per cob is 36,49 grain or 7,3% of normal production grain per cob.